2001
DOI: 10.1055/s-2001-14544
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Disease: Risk Factors and Laboratory Investigation

Abstract: The etiology of venous thromboembolic disease has been the subject of several recent discoveries, particularly on genetic predisposing factors. The laboratory investigation that may help to evaluate the risk for individual patients includes the measurements of coagulation inhibitors (antithrombin, protein C, and protein S) in plasma assays, the search for the factor V Leiden mutation by the plasma activated protein C resistance test (always to be confirmed by DNA analysis when abnormal), and the search for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…However, the correlation between FXI plasma levels and bleeding tendency is low. On the other hand, it is suggested that an increased FXI level is a risk factor for thrombosis [121]. Thrombus formation upon ferric chloride induced injury of the carotid artery was defective in FXI-deficient mice [122] and could be restored by injection of exogenous FXI.…”
Section: The Gpib-ix-v Complex As a Receptor For Coagulation Factor XImentioning
confidence: 99%
“…However, the correlation between FXI plasma levels and bleeding tendency is low. On the other hand, it is suggested that an increased FXI level is a risk factor for thrombosis [121]. Thrombus formation upon ferric chloride induced injury of the carotid artery was defective in FXI-deficient mice [122] and could be restored by injection of exogenous FXI.…”
Section: The Gpib-ix-v Complex As a Receptor For Coagulation Factor XImentioning
confidence: 99%
“…We preferred an exponential allocation of a risk magnitude to an even one because the risk of VTE significantly increases if several causative factors are present at the same time. In this case, the individual odds ratios are not simply added but are multiplied by each other 1,2 . We recommend adequate clinical prevention steps pursuant to every risk range.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mutation in factor V Leiden or prothrombin genes, deficiency of antithrombin, protein C or S, hyperhomocysteinemia, high concentrations of factors VIII, IX or XI, antiphospholipid syndrome, disfibrinogenemia, and abnormal fibrinolysis are prominent laboratory risk factors. Combination of several factors increasing the risk of VTE in one patient at the same time is common 1,2 . Risk of VTE is increased in psychiatric patients as compared to mentally healthy people, 3,4 especially in schizophrenia and bipolar disorder 5 .…”
mentioning
confidence: 99%
“…In this case, the individual odds ratios are not simply added, but multiplied by each other [13,14]. Even if some researchers propose the possibility that VTE may be associated with schizophrenia itself via autoimmune mechanisms [15] or increased homocysteine serum level [16] instead of the medication, we do not suppose that the mental disorder led to thrombosis.…”
Section: Discussionmentioning
confidence: 99%